Effect of integrated nutrient management on growth, yield and quality attributes of black cumin (Nigella sativa L.) var. Rajendra Shyama grown under terai region of West Bengal - P Choudhury, A Sen, S D Khade, J C Jana, (Journal of Spices and Aromatic Crops, 2019)
A field experiment was conducted during rabi seasons of 2014–15 and 2015–16 to study the effects of various combination of different levels of inorganic, organic and bio-fertilizers (Azophos) on the vegetative growth, yield contributing attributes and quality of seeds of black cumin. The results showed that the combination of 100% RDF (Recommended Dose of Fertilizer) + 15 t ha-1 FYM (Farm Yard Manure) + 4 kg ha-1 Azophos significantly improved most of the parameters related to growth of plant, seed yield and net returns. However, for production of seed oil, 75% RDF of chemical fertilizers + FYM + bio-fertilizer was recorded was the best. Most of the soil properties were improved by application of 100% RDF + FYM. Therefore from the results, it could be suggested that inclusion of organic manure and bio-fertilizer along with 100% (RDF) is the best combination for seed production of black cumin whereas for better quality seed oil 25% RDF can be substituted with FYM and biofertilizer (Azophos) in terai region of West Bengal.